Edukasi Nasionalisme dalam Peringatan Hari Pahlawan : Pendampingan Kegiatan Kebangsaan di Desa Lebani Suko Kedamean Gresik - Nanang Abdillah; Ria Resti Fauziah; Ary Rachman; Naungi Atkin Insan Agamis; Moch Yogie Firmansah; Nurul Hafidho; Nina Nathania; Anin Naimatus Naini; Siti Mustikawati; Qomairoh Qomairoh (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
This research examines the mentoring of nationalistic activities by students from the Al-Azhar Menganti Gresik Institute and field supervisors at MI Darunnajah Lebani Suko, Wringinanom District, Gresik Regency, in commemoration of Heroes' Day. Thru a descriptive qualitative approach, this program involves four main activities: the red and white parade, patriotic love songs, little warrior strokes (coloring and writing hero stories), and a colossal drama of patriotic fervor. These activities are creatively designed and based on direct experience to instill nationalistic values in elementary school students. The research results show a significant improvement in students in terms of courage, discipline, creativity, cooperation, and respect for national symbols such as the flag and national anthem. Collaboration between students as facilitators, teachers as pedagogical directors, and the school environment creates a conducive learning ecosystem where participatory methods are more effective than conventional approaches. This experiential learning approach not only enhances cognitive understanding of the struggles of national and local heroes but also builds emotional empathy and social skills. Positive impacts include high student enthusiasm, reduced learning boredom, and character strengthening in accordance with the Pancasila Student Profile, such as mutual cooperation and integrity. Overall, this mentoring program serves as a relevant model for non-formal character education that can be replicated in other schools to strengthen nationalism from an early age amidst the challenges of post-pandemic globalization and individualism.